2021
DOI: 10.3390/su132011248
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impacts Associated with Intensive Production in Pig Farms in Mexico through Life Cycle Assessment

Abstract: In this research, environmental impacts associated with the intensive production of pigs on a farm in Mexico were determined through the application of life cycle assessment methodology. The research was focused on the following stages of the product system: (i) pig rearing and growth phases; (ii) production operations in the pig-house; (iii) the supply of feed. The life cycle inventory database was mainly made up of data collected in field visits to local farms. The functional unit was defined as one finished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
0
4
0
1
Order By: Relevance
“…These are some of many international transactions that take place in the world economy for satisfying EU's demand for food, in turn resulting in spillover effects (Figures 3, 4). The agri-food sector is contributing to environmental pressures worldwide, for example, quinoa demand in Peru is driving land use impacts (Bedoya-Perales et al, 2018), agriculture is contributing to degradation of water quality in Brazil (de Mello et al, 2020), cocoa production in Ghana has implications for soil, air and water quality (Boakye-Yiadom et al, 2021), environmental impacts from livestock farming in Mexico (Giraldi-Díaz et al, 2021), impacts related to biodiversity and ecotoxicity from beef production in Argentina (Fischer & Bilenca, 2020), soil erosion in Kenya due to agricultural expansion (Maeda et al, 2010). These are just selected examples that demonstrate the wide-ranging impacts driven by the agri-food sector, and the need to devise strategies for ensuring that livelihoods can be sustained without putting pressures on Earth's ecosystems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are some of many international transactions that take place in the world economy for satisfying EU's demand for food, in turn resulting in spillover effects (Figures 3, 4). The agri-food sector is contributing to environmental pressures worldwide, for example, quinoa demand in Peru is driving land use impacts (Bedoya-Perales et al, 2018), agriculture is contributing to degradation of water quality in Brazil (de Mello et al, 2020), cocoa production in Ghana has implications for soil, air and water quality (Boakye-Yiadom et al, 2021), environmental impacts from livestock farming in Mexico (Giraldi-Díaz et al, 2021), impacts related to biodiversity and ecotoxicity from beef production in Argentina (Fischer & Bilenca, 2020), soil erosion in Kenya due to agricultural expansion (Maeda et al, 2010). These are just selected examples that demonstrate the wide-ranging impacts driven by the agri-food sector, and the need to devise strategies for ensuring that livelihoods can be sustained without putting pressures on Earth's ecosystems.…”
Section: Resultsmentioning
confidence: 99%
“…and water quality (Boakye-Yiadom et al, 2021), environmental impacts from livestock farming in Mexico (Giraldi-Díaz et al, 2021), impacts related to biodiversity and ecotoxicity from beef production in Argentina (Fischer & Bilenca, 2020), soil erosion in Kenya due to agricultural expansion (Maeda et al, 2010). These are just selected examples that demonstrate the wideranging impacts driven by the agri-food sector, and the need to devise strategies for ensuring that livelihoods can be sustained without putting pressures on Earth's ecosystems.…”
Section: International Spillovers: Country and Sector Levelmentioning
confidence: 99%
“…In particular, it has been reported that intensive pig rearing generates approx. 10% of GHG emissions from livestock, which is the second highest in this sector (Giraldi-Díaz et al, 2021); in addition, environmental issues associated with pig production concern water and air pollution (Rodhe et al, 2012). Pig slurry contains harmful substances, such as heavy metals, unpleasant odours, parasites, and pathogens that pose potential risks to the environment and public health, especially when improperly treated and applied (Sun et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…c Proportion of energy generated for self-consumption from production plants. Source: own elaboration with information from[55][56][57][58].…”
mentioning
confidence: 99%